THE EFFECT OF ORGANIC SEDIMENT CONTENT ON CORAL DIVERSITY IN KARIMUNJAWA ISLAND, INDONESIA - Fajar Nugroho; Neviaty P. Zamani; Hawis Madduppa (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2018)
Coral reef now are under threats due to sedimentation. Fatal effect of organic rich sediment, leading corals mortality. Therefore, the study was conducted to investigate effect of organic sediment content to the coral diversity in Karimunjawa Island, Central Java, Indonesia. Field data was conducted at 6 locations. Three sediment traps were deployed at each sites to measure organic sediment content. Twenty replicated quadrant transects were used to estimate coral density and coral diversity. Analysis of variance (ANOVA) was used to examine the differences of organic sediment content in each station. The linear regression was used to assess the relationship between organic sediment content and coral diversity. Our field result demonstrated that sediment content significantly different between sites with value range from 0.42 mg/800 ml - 1.32 mg/800 ml. Based on the Simson’s Diversity Index, the highest coral diversity found at Alang-alang as site with low sedimentation while the lowest coral diversity was found at Legon Lele as site with high sedimentation. The study shown significant negative correlation between organic sediment content and coral diversity with the coefficient of regression 0.68. This study convinces that disturbance on coral reefs might affect coral diversity in Karimunjawa Island, in addition to other factors such as the influence of human activities, natural disruption and climate change. Keywords: sedimentation, organic, coral, diversity, Karimunjawa